ESTUDOS ESTRUTURAIS DA ENZIMA HISTIDINA AMÔNIO LIASE DE Trypanosoma cruzi - Miranda, Robson Rodrigo (2015)
Chagas disease is one of the seventeen neglected tropical diseases according to the World Health Organization. In the recent decades, new parasite metabolic pathways were identified, what brings perspectives for the development of more specific and less toxic drugs, towards crucial target pathways. Once the therapeutic target is identified, a structural and biochemical characterization of the enzymes involved becomes necessary. It may be speculated that one possible therapeutic target to combat Chagas disease is the Histidine Ammonia-Lyase enzyme, which participates in the catabolic pathway of histidine. Therefore, in order to contribute to the structural and biochemical understanding of this enzyme, their heterologous production in E. coli was performed. The product protein was purified by affinity chromatography and used in various techniques for initial characterization. The activity was determined by kinect assay, the thermal stability and secondary structure content were investigated by Circular Dichroism (CD) and the oligomerization stated in solution was analyzed by Dynamic Light Scattering (DLS). The X ray diffraction technique was used to elucidate the three dimensional structure. TcHAL was expressed and purified satisfactorily. The activity proved adequate protein folding and the Circular Dichroism indicated a predominance of α-helix secondary structure and the start of the thermal denaturation at 68°C. TcHAL was crystallized and provided suitable diffraction patterns for the 3D structure elucidation. These biochemical and structural studies advanced the understanding of this enzyme and of the inhibition potentialities.